1998
DOI: 10.1002/(sici)1521-3765(19980615)4:6<1016::aid-chem1016>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The 55 % Solution: A Formula for Molecular Recognition in the Liquid State

Abstract: Evidence is presented that molecular recognition through encapsulation processes is largely determined by the volumes of the guest and host. Binding of molecules of suitable dimensions in the internal cavity of a molecular receptor in solution can be expected when the packing coefficient, the ratio of the guest volume to the host volume, is in the range of 0.55 AE 0.09. Larger packing coefficients, up to 0.70, can be reached if the complex is stabilized by strong intermolecular forces such as hydrogen bonds. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

80
761
5
17

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 838 publications
(863 citation statements)
references
References 15 publications
80
761
5
17
Order By: Relevance
“…A similar calculation for L9A+IB again results in an occupation value of about 60%. These fractional occupation values agree closely with the ideal encapsulation value of 55 ± 9% reported by Rebek and coworkers (45). The cavities within the L9A and L9G structures increase in volume by about 20 Å 3 when occupied by iodobenzene (Table 2).…”
Section: Iodobenzene Bindingsupporting
confidence: 89%
“…A similar calculation for L9A+IB again results in an occupation value of about 60%. These fractional occupation values agree closely with the ideal encapsulation value of 55 ± 9% reported by Rebek and coworkers (45). The cavities within the L9A and L9G structures increase in volume by about 20 Å 3 when occupied by iodobenzene (Table 2).…”
Section: Iodobenzene Bindingsupporting
confidence: 89%
“…[21] Although this is significantly lower than the optimal 55 % packing efficiency, [22] it is in excellent agreement with thẽ 43 % occupancy recently calculated for the eight benzene guest molecules observed within the resorcin [4]arene/water Archimedean snub cube. [10] We have shown that a small structural variation-in this case the extension of an alkyl chain by one carbon atom-in the pyrogallol [4]arenes can have profound effects on the crystal packing and interactions between nanocapsules.…”
supporting
confidence: 82%
“…E-mail: jrebek@scripps. each) occupy Ϸ52% of the capsule's space (420 Å 3 ), and the capsule is optimally filled (10).…”
Section: Resultsmentioning
confidence: 80%